Wavelet Analysis of Ultrasonic Lamb Wave Displacements in Three-Layer Adhesive Plates: Continuous Wavelet Transform (CWT) versus the Semi-Analytical Finite Element Method (SAFEM) - YACOUBI, Abdelali; JABIRI, Ayoub; AZKOUR, Mustapha; MANDRY, Rachid; EL ALLAMI, Mhammed (Engineering Transactions, 2024)
In this paper, we aim to identify the most appropriate mother wavelet for analyzing the displacements of ultrasonic guided waves in tri-layered adhesive plates.We determine the group velocities of a given mode using various mother wavelets. The precision of each mother wavelet is evaluated by comparing the values of the group velocities with those found by the semianalytical finite element method (SAFEM). The most appropriate mother wavelet function can then be used to study tri-layered adhesive plates with defects.